How highly creative product descriptions lead to attitude change: a dual-process model - Yao, Feisi; Shao, Jingbo (Journal of cognitive psychology (Hove, England), 2021)
This study employs a heuristic-systematic model to examine the internal mechanisms responsible for the persuasiveness of text descriptions that are high (vs. low) in creativity, and their effect on consumers' attitudes toward products. It also examines the moderating role of trust cues. We theorised and demonstrated via three between-subjects design experiments that text descriptions high in creativity can be perceived as providing a heuristic signal of style and systematic information regarding their content. Furthermore, perceived effort and perceived message strength mediated the persuasiveness of text descriptions high in creativity in parallel, as measured by consumers' attitudes. Moreover, the positive valence of the mediating role depended on trust cues. The present study reveals a novel dual-process model of the persuasiveness of text descriptions high (vs. low) in creativity and identifies the boundary condition. The implications of these findings for consumer decision-making and firms seeking to manage online product presentation are discussed.